WEB-Enabled Medical Databases: a Threat to Security? - Herrin, J.; Dempsey, B. J., III (Methods of Information in Medicine, 2000)
An increasing number of clinical databases are being adapted to allow access through Internet protocols, particularly Hypertext Transfer Protocol (HTTP). The World Wide Web (WWW) provides a user-friendly, standardized, broadly distributed database interface; at the same time, it may also present a threat to the security and confidentiality of patient data. However, there is little empirical evidence concerning such threats. Using publicly available records we estimate the additional risk of security violations due to web-enabling a database. The evidence, though limited, suggests that the additional risk may be small relative to more traditional security threats.
Keywords: Medical Database Security; Information System Security; Database Security; Internet